2013
DOI: 10.1590/s1413-35552012005000066
|View full text |Cite
|
Sign up to set email alerts
|

Effect of treadmill gait training on static and functional balance in children with cerebral palsy: a randomized controlled trial

Abstract: | Background: Treadmill gait training as a therapeutic resource in the rehabilitation of children with cerebral palsy has recently been the focus of many studies; however, little is still known regarding its effect on static and functional balance in children. Objective: The aim of the present study was to compare the effects of treadmill training and over ground gait training in children with cerebral palsy. Method: A randomized controlled trial with blinded evaluator was conducted with children with cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 29 publications
1
37
0
5
Order By: Relevance
“…Balance deficit resulting in frequent falls is one of the most limiting aspects of CP13 , 26 , 27. Regarding oscillations of the CoP, two important findings were identified in the present study: 1) the similarity in the results with and without visual restriction; and 2) although a small number of participants were classified at level III of the GMFCS (three per group), the effects apparently involved these children, who require gait-assistance devices.…”
Section: Discussionmentioning
confidence: 99%
“…Balance deficit resulting in frequent falls is one of the most limiting aspects of CP13 , 26 , 27. Regarding oscillations of the CoP, two important findings were identified in the present study: 1) the similarity in the results with and without visual restriction; and 2) although a small number of participants were classified at level III of the GMFCS (three per group), the effects apparently involved these children, who require gait-assistance devices.…”
Section: Discussionmentioning
confidence: 99%
“…Stabilometric analysis is one of the most reliable ways to assess static balance and provides valid information on the oscillation of the center of pressure3 ) . This assessment was included in the present case due to the fact that postural stability is a well-defined prerequisite for motor development in children.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated the positive effects of treadmill training in children with gait impairment1, 3, 4 ) . Despite the small amount of evidence regarding the use of treadmill training on children under six years of age, systematic reviews have reported encouraging results, with improvements in gait velocity, muscle strength and gross motor function1 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Sixty to eighty percent maximal tolerance reached on the initial treadmill test was used for the training sessions. Walking speed was at 60% maximal speed in the first and terminal five minutes of each session and at 80% maximal speed for the other 20 minutes [14] (Figure 1). data was compared between groups by t-test (P 0.05).…”
Section: Methodsmentioning
confidence: 99%